1966
DOI: 10.1063/1.1727656
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Paramagnetic Resonance Spectra of Some Trigonal Co(II) Chelates

Abstract: Paramagnetic resonance has been observed at 4.2°K in magnetically dilute single crystals and powders of bis[hydrotris(1-pyrazolyl)borate]Co(II) and bis[tris(1-pyrazolyl)methane]Co(II) chelate systems. The chelate structure for both types of compound has D3d symmetry, and the principal g tensor components show large axial anisotropy. In conjunction with optical data for these complexes, the results are analyzed in terms of the theory of Abragam and Pryce. In addition to the experimentally determined g values fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
63
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 17 publications
15
63
0
Order By: Relevance
“…55 The presence of three electrons in two nearly degenerate e g orbitals is expected to lead to a large anisotropy, in this case it produces a uniaxial magnetic anisotropy as confirmed by EPR analysis 50 years ago. 56 Thus far, however, no SMMs have been reported with this geometry. We postulated that fac -tripodal ligands could enforce a trigonal antiprismatic geometry, thus we undertook a systematic study of Co( ii ) complexes equipped with tris(pyrazol-1-yl)methane (Fig.…”
Section: Introductionmentioning
confidence: 90%
“…55 The presence of three electrons in two nearly degenerate e g orbitals is expected to lead to a large anisotropy, in this case it produces a uniaxial magnetic anisotropy as confirmed by EPR analysis 50 years ago. 56 Thus far, however, no SMMs have been reported with this geometry. We postulated that fac -tripodal ligands could enforce a trigonal antiprismatic geometry, thus we undertook a systematic study of Co( ii ) complexes equipped with tris(pyrazol-1-yl)methane (Fig.…”
Section: Introductionmentioning
confidence: 90%
“…Using ligand field theory, Abragam and Pryce (15) have shown that the Co(I1) ground term 4F is split by an octahedral field producing a 4Tlg ground state. Because there is strong spin-orbit coupling, this 4Tlg state is further split into six doubly degenerate levels (Kramer's doublets) (16,17) with ! 'Author to whom correspondence may be addressed.…”
mentioning
confidence: 99%
“…One of the most favourable molecules for studying the details of second sphere structure is bis[hydrotris(1-pyrazoyl)borato]cobalt(II) [48] the structure of which is shown in Figure 3 crystal field [49] is particularly susceptible to large g value anisotropies which lead to large dipolar chemical shifts for nuclei close to the paramagnetic metal ion. In this case gll = 8.46 and g± = 0.98 [50] which is an exceptionally large anisotropy.…”
Section: K= Yayb/ybyamentioning
confidence: 99%